2011
DOI: 10.1095/biolreprod.111.091850
|View full text |Cite
|
Sign up to set email alerts
|

Stem Leydig Cell Differentiation: Gene Expression During Development of the Adult Rat Population of Leydig Cells1

Abstract: Leydig cells are the testosterone-producing cells in the adult male. Adult Leydig cells (ALCs) develop from stem Leydig cells (SLCs) through at least two intermediate cells, progenitor Leydig cells (PLCs) and immature Leydig cells (ILCs). Microarray gene expression was used to identify the transcriptional changes that occur with the differentiation of SLCs to PLCs and, thus, with the entry of SLCs into the Leydig cell lineage; to comprehensively examine differentiation through the development of ALCs; and to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 36 publications
(55 reference statements)
6
57
0
1
Order By: Relevance
“…CD51 and p75NTR also are cell surface proteins whose expressions were found to overlap with that of nestin in the neonatal mouse testis (11). By reanalysis of an earlier array study (13), we also identified a number of cell surface proteins whose mRNAs were highly expressed by stem cells but turned off with the transit of these cells to progenitor Leydig cells.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 68%
See 1 more Smart Citation
“…CD51 and p75NTR also are cell surface proteins whose expressions were found to overlap with that of nestin in the neonatal mouse testis (11). By reanalysis of an earlier array study (13), we also identified a number of cell surface proteins whose mRNAs were highly expressed by stem cells but turned off with the transit of these cells to progenitor Leydig cells.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 68%
“…In an earlier study, we had conducted microarray analysis of gene expression during the differentiation of neonatal stem Leydig cells to cells that entered the Leydig cell lineage as progenitor Leydig cells (13). The significantly up-regulated or down-regulated genes for signaling molecules and receptors were among those in which we took particular interest.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 99%
“…Microarray analysis of transcripts from isolated adult rat Leydig cells by Stanley et al (2011) showed the presence of 16 713 specific species (not allowing for duplicates on Leydig cell mRNA transcripts the arrays). Most of these transcripts will not be unique to the Leydig cells, but a degree of specificity can be estimated by determining the relative enrichment of these transcripts in comparison to our control wholetestis arrays.…”
Section: Comparison To Other Testicular Cell Transcript Databasesmentioning
confidence: 99%
“…This is consistent with a predominant Leydig cell expression of transcripts listed in Table 1. Stanley et al (2011) also identified 42 genes upregulated during Leydig cell development and, of these genes, 17 are also included in Supplementary Table 2, including eight of the top 11 genes we identified. When the same 42 genes identified by Stanley (2011) were compared with the full list of transcripts significantly altered by EDS (Supplementary Table 1), the number of matches increased to 23 although most of the additional six matches showed either low expression or complex changes in expression after EDS treatment (Supplementary Table 3, see section on supplementary data given at the end of this article).…”
Section: Comparison To Other Testicular Cell Transcript Databasesmentioning
confidence: 99%
See 1 more Smart Citation